Multiresolution Time-Domain Analysis of Multiconductor Transmission Lines Terminated in Linear Loads. (20th March 2017) - Tong, Zongliang; Sun, Lei; Li, Ying; Angulo, Luis Diaz; Garcia, Salvador Gonzalez; Luo, Jianshu
Abstract : This paper derives a multiresolution time-domain (MRTD) scheme for the multiconductor transmission line (MTL) equations based on Daubechies' scaling functions. The terminations are characterized by a state-variable formulation which allows a general description of the termination networks. For the linear load terminations, a method incorporating the terminal constraints is proposed to work out the scheme at and close to the terminations. The MRTD scheme is implemented with different basis functions for linear components including resistances, inductances, and capacitances. Numerical results show that the MRTD schemes obtain a more stable result than the conventional finite difference time-domain (FDTD) method with a coarse space step.